Hippocampus, Amygdala, and Thalamus Volumes in Very Preterm Children at 8 Years: Neonatal Pain and Genetic Variation - Chau, Cecil M. Y.; Ranger, Manon; Bichin, Mark; Park, Min Tae M.; Amaral, Robert S. C.; Chakravarty, Mallar; Poskitt, Kenneth; Synnes, Anne R.; Miller, Steven P.; Grunau, Ruth E. (Frontiers in Behavioral Neuroscience, 2019)
Altered hippocampal morphology and reduced volumes have been found in children born preterm compared to full-term. Stress inhibits neurogenesis in the hippocampus, and neonatal stress/noxious stimulation in rodent pups are associated with long-term alterations in hippocampal volumes. We have previously shown reduced cortical thickness and cerebellar volumes in relation to more exposure to pain-related stress of neonatal invasive procedures in children born very preterm. We have reported targeted gene-by-pain environment interactions that contribute to long-term brain development and outcomes in this population. We now aim to determine whether exposure to pain-related stress (adjusted for clinical factors and genotype) differentially impacts regional structures within the limbic system and thalamus, and investigate relationships with outcomes in very preterm children. Our study included 57 children born very preterm (<32 weeks GA) followed longitudinally from birth who underwent 3-D T1 MRI neuroimaging at ~8 years. Hippocampal subfields and white matter tracts, thalamus and amygdala were automatically segmented using the MAGeT Brain algorithm. The relationship between those subcortical brain volumes (adjusted for total brain volume) and neonatal invasive procedures, gestational age (GA), illness severity, postnatal infection, days of mechanical ventilation, number of surgeries, morphine exposure, and genotype (COMT, SLC6A4, BDNF) was examined using constrained principal component analysis. We found that neonatal clinical factors and genotypes accounted for 46% of the overall variance in volumes of hippocampal subregions, tracts, basal ganglia, thalamus and amygdala. After controlling for clinical risk factors and total brain volume, greater neonatal invasive procedures was associated with lower volumes in the amygdala and thalamus (p = 0.0001) and an interaction with COMT genotype predicted smaller hippocampal subregional volume (p = 0.0001). More surgeries, days of ventilation, and lower GA were also related to smaller volumes in various subcortical regions (p < 0.002). These reduced volumes were in turn differentially related to poorer cognitive, visual-motor and behavioral outcomes. In very preterm children, higher exposure to pain and stress of neonatal invasive procedures, as well as clinical factors and genotypes were associated with reduced volumes in hippocampal subregions, basal ganglia, amygdala and thalamus, which in turn were related to poorer outcomes at school age.